Fetal and Neonatal Outcomes After Term and Preterm Delivery After Betamethasone Administration in Twin Pregnancies. Issue 2 (February 2017) - Braun, Thorsten; Weichert, Alexander; Gil, Hannah C.; Sloboda, Deborah M.; Tutschek, Boris; Harder, Thomas; Dudenhausen, Joachim W.; Plagemann, Andreas; Henrich, Wolfgang
Abstract : (Abstracted from Int J Gynaecol Obstet 2016;134:329–335) Prenatal betamethasone administration in singleton pregnancies is associated with a dose-dependent decrease in birth weight. This study aimed to determine the effects of betamethasone overall, and at different doses on fetal growth and neonatal outcomes in twin pregnancies based on fetal sex, chorionicity, and severity of prematurity.